Técnicas anestésicas injetáveis em capivaras (Hydrochoerus hydrochaeris, Linné) - Cruz, Mariângela Lozano [UNESP] (1998)
The aim of this study was to investigate three anaesthetic techniques in capybaras. Twenty three male and 27 female adult capybaras weighing 36 ± 7 kg were divided in three groups: G 1(n =20) - xylazine (1mg/kg) and ketamine (20mg/kg), G2 (n=l5) - midazolam (0,5mg/kg) and ketamine (20mg/kg) and G3 (n=15) - romifidine (0,1 mg/kg) and ketamine (20mg/kg). All drugs were given intramuscularly in the same syringe using darts. Heart and respiratory rates and temperature were evaluated every 15 minutes for 60 minutes after the administration of the anaesthetics. Time to onset of action, duration of analgesia and recovery period were also measured. Five out of 20 animals from G 1died during the experiment. Duration of analgesia and recovery was longer after xylazine and ketamine and shorter after midazolam and ketamine. Heart rate decreased in G1 and G3. There was no change in respiratory rate. Temperature decreased in all groups. Tattoo mark, earring placing and venous punction was performed in all animals using these anaesthetic protocols. Special care should be taken when xylazine is used under a high environmental temperature and further studies should be performed in order to evaluate the ideal dose of midazolam in capybaras.